1980
DOI: 10.1128/jvi.33.3.1097-1105.1980
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activities of different phosphorylated species of NS protein purified from vesicular stomatitis virions and cytoplasm of infected cells

Abstract: Vesicular stomatitis virus contains a phosphorylated NS protein which is necessary along with L protein and RNP template for transcription of mRNA. To further define the structure of the NS protein and its function in transcription and replication, virion NS was purified and separated into two different phosphorylated forms (NSI and NSII) on DEAE-cellulose columns. Cytoplasmic preparations of NS contained one phosphorylated species which eluted from the column in the same place as the virion NSI. When electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…P protein from infected cells or purified virions was readily separated by gel electrophoresis or ion exchange chromatography into two fractions, which generally differed both in average degree of phosphorylation and in transcriptional activity. Differences were found between cell and viral P protein, and between fractions separated by several different techniques, adding further to the aura of complexity (Clinton et al, 1979;Kingsford and Emerson, 1980;Barik and Banerjee, 1992a).…”
Section: Discussionmentioning
confidence: 98%
“…P protein from infected cells or purified virions was readily separated by gel electrophoresis or ion exchange chromatography into two fractions, which generally differed both in average degree of phosphorylation and in transcriptional activity. Differences were found between cell and viral P protein, and between fractions separated by several different techniques, adding further to the aura of complexity (Clinton et al, 1979;Kingsford and Emerson, 1980;Barik and Banerjee, 1992a).…”
Section: Discussionmentioning
confidence: 98%
“…It also interacts with the N protein to form N-P complexes that are required for encapsidation of nascent RNA chain during replication (34,47). In virus-infected cells as well as in the virion core, the P protein has been shown to exist in multiple phosphorylated forms (7,14,27,28,32,41). In this study, we examined the role of phosphorylation within the amino-terminal acidic domain I of the P protein of VSV (Indiana serotype) in transcription and replication under in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it interacts with specific nucleotide sequences at the termini of VSV genome, presumably for transcription and replication (29,31). The P protein is found in different phosphorylated forms in infected cells as well as in the virion core, and different functional forms of P protein with different degrees of phosphorylation have been shown to exist (7,14,27,28,32,41). A direct role of phosphorylation in P-protein function was provided by the studies of Chattopadhyaya and Banerjee (12), who demonstrated that phosphorylation within a specific domain regulates the function of P protein in transcription in vitro.…”
mentioning
confidence: 99%
“…The studies related to the phosphorylated state of the NS protein as well as to the role of NS phosphorylation in transcription and replication have been accumulating for several years. There are a number of reports which indicate that inhibition of in vitro phosphorylation of NS protein by various compounds results in the inhibition of VSV RNA synthesis in vitro (48,119,120,192,206,236,244). However, the cogent question still remains unanswered as to the precise location of the functional phosphorylation sites within the NS molecule.…”
Section: Structure and Function Of Ns Proteinmentioning
confidence: 99%